2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6091587
|View full text |Cite
|
Sign up to set email alerts
|

Development and usability testing of a parent decision support tool for the neonatal intensive care unit

Abstract: In this paper we present the development and evaluation of a parent decision support tool for a neonatal intensive care unit (NICU), known as PPADS or Physician and Parent Decision Support. The NICU interprofessional (IP) team uses advanced technology to care for the sickest infants in the hospital, some at the edge of viability. Many difficult care decisions are made daily for this vulnerable population. The PPADS tool, a computerized decision support system, aims to augment current NICU decision-making by he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…Most included studies evaluated patient and/or caregiver information needs to design and/or enhance inpatient portals. 16,2437 In 1 study, patients described an overall lack of information provided in the hospital and insufficient time to understand and remember information, which, when shared, was often presented by using medical terminology. 30 They wanted information to help them understand their daily hospital routine, confirm and compare medications and test results, learn about care, and prepare for discharge.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most included studies evaluated patient and/or caregiver information needs to design and/or enhance inpatient portals. 16,2437 In 1 study, patients described an overall lack of information provided in the hospital and insufficient time to understand and remember information, which, when shared, was often presented by using medical terminology. 30 They wanted information to help them understand their daily hospital routine, confirm and compare medications and test results, learn about care, and prepare for discharge.…”
Section: Resultsmentioning
confidence: 99%
“…Most patient and/or caregiver participants in included studies were interested in using an inpatient portal, used it when offered, found it easy to use, useful, and/or were satisfied with it. 16,18,2437 Most used and liked functionalities that provided healthcare team, test result, and medication information. 22,33,37 In the 1 identified controlled trial, 18 researchers evaluated an inpatient portal given to adult inpatients that included a problem list, schedule, medication list, and healthcare team information.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that integrating users’ evaluation of each Dbox in a feedback loop is essential and that using the Dbox template alone, although helpful to optimize the overall design of the Dbox, is not sufficient to ensure that the content matches all of the user’s decision-making and reasoning skills and information-processing needs. Iterative development, one principle of usability testing, is used increasingly in health care [ 54 - 56 ] and allows users to partake in designing communication materials that are not only readable and understandable but also engaging and actionable [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few researchers have looked at technologies for caregivers of young patients in hospital wards, such as the neonatal intensive care unit (NICU), where parents who are physically separated from their child require access to clinical information to make decisions about care or treatment [1,24,36]. Except for these specific contexts, little is known about caregivers as users of patient engagement technologies in the hospital.…”
Section: Related Workmentioning
confidence: 99%